Analisis Peningkatan Kualitas Pelayanan Dengan Metode Quality Function Deployment Studi Pada Bank Sumut Kcp Syariah Stabat - Puspita, Rini; Marliyah, Marliyah; Nasution, Juliana (AGHNIYA : Jurnal Ekonomi Islam, 2023)
This research was conducted to analyze the quality of services provided by Bank Sumut KCP Syariah Stabat to its customers. The purpose of this study is to see the quality of service provided by the bank using the QFD method in meeting the expectations of its customers, and to see which attributes should be prioritized and improved in the service system. The method used in this study is the Quality Function Deployment (QFD) method assisted by data analysis techniques using SPSS to process the data distributed through a Likert scale-based questionnaire to 100 respondents. The results of this study explain that with the QFD method the customer's expectations that are prioritized are employees who take the time to respond to customer requests. This must be corrected by the bank so that service satisfaction meets customer expectations. In the HOQ matrix it is shown that the technical aspects that are interacted with the customer's preferred attributes have a priority value of 420 with technical responses doing work according to the SOP. This proves that if all services run according to the SOP, the quality of service will also increase.